Sub-chronic safety evaluation of aqueous extract of Alangium salvifolium (L.f.) Wangerin leaves in rats - Bhupinder Kapoor; Gagandeep Kaur; Mukta Gupta; Reena Gupta (Wolters Kluwer Medknow Publications, 2017)
Conventionally, the juice and extract of Alangium salvifolium leaves have been used for the treatment of diabetes, wound healing, dog bite, and as a poultice in rheumatism. To carry out the sub-chronic toxicity and thereafter safety evaluation of A. salvifolium leaves. The aqueous extract of A. salvifolium leaves was administered orally at the doses of 200, 400, and 800 mg/kg/day for 90 days. All the animals were observed daily for general behavior, changes in body weight, food, and water consumption. At the end of the treatment period, biochemical and hematological parameters were analyzed; and the animals were sacrificed for histopathological examination of heart, lungs, liver, and kidney. The general behavior and water intake were normal in all the rats. The increase in body weight was observed in female rats of all the groups while body weight was decreased in high dose group animals of both sexes. Hematological parameters were not disturbed by the continuous use of extract. A significant decrease in glucose level was observed in intermediate- and high-dose group animals while urea and creatinine level were significantly high in animals of high-dose group. Although histopathological examination of most of the organs exhibited no structural changes, some tubal damage in kidneys was observed in high-dose group animals. The high dose of extract has shown mild signs of toxicity on kidney function test, but no toxic response was observed on hematological and liver biochemical parameters. The extract also exhibited hypoglycemic potential.